Genetic relationships between some of Malva species as determined with ISSR and ISJ markers - Celka, Zbigniew; Szczecińska, Monika; Sawicki, Jakub (Biodiversity: Research and Conservation, 2011)
Two categories of DNA markers were used to determine genetic relationships among eight Malva taxa. A maximum parsimony analysis validated the division of the genus Malva into the sections Bismalva and Malva. The species classified into those sections formed separate clusters. M. moschata was a distinctive species in the section Bismalva, as confirmed by previous genetic research based on ITS and cpDNA sequence analyses. The applied markers revealed a very high level of genetic identity between M. alcea and M. excisa and enabled molecular identification of M. alcea var. fastigiata. Speciesspecific markers were determined for the majority of the analyzed species, permitting their molecular identification. A specific marker supporting the differentiation of M. alcea and M. excisa was not found.